Alternatif mortgage teknikleri ve Türkiye uygulaması - Eroğlu, Erhan (My University, 2007)
Konut finansmanının temel amacı, konut sahibi olmak isteyen kişilere, kendi konutlarını satın almak için ihtiyaç duydukları fonları sağlamaktır. Bu amaç doğrultusunda yeterli fona sahip olmayan kişiler ya dolaysız finansman yöntemini kullanarak yakın akraba veya arkadaş çevresinden borç alacak ya da ipotek kredisi veren kurumlara başvurarak, gerekli inceleme ve değerlendirmeler sonucu satın aldığı konuta ipotek konularak (kredi alarak) fon temin edebileceklerdir. Genel olarak ipotek piyasası denildiğinde, hem birinci el hem de ikinci el ipotek piyasası ifade edilmektedir. Birinci el piyasada konut ipotek kredileri düzenlenmekte, ikinci el piyasada ise düzenlenmiş olan bu krediler işlem görmekte, diğer bir değişle alınıp satılmaktadır. Düzenlenmiş olan ipotek kredilerinin biraraya toplanması suretiyle oluşturulan ipotek havuzuna dayalı olarak ihraç edilen menkul kıymetlere ipoteğe dayalı menkul kıymetler (Mortgage Backed-Securities - MBS) denilmektedir. İpoteğe dayalı menkul kıymetler bazen ipotekten geçen menkul kıymetler olarak da adlandırılırlar. Bir konut finansman sistemi olarak mortgage.ın doğrudan konut kredisi sisteminden farkı, fonlama açısından kendine yeterli olması ve sistemin kendini besleyebilmesidir. Mortgage sisteminde bankaların ve yetkili diğer finansal kuruluşların ipotek karşılığı verdikleri krediler için havuzlar oluşturulur. Bu havuzlara tüketiciler tarafından yapılacak anapara ve faiz geri ödemeleri karşılığında düzenlenen menkul kıymetler, sermaye piyasalarında yatırımcılara arz edilerek toplanan fonlar yeniden konut kredilerine dönüşür. Ülkemizde konut almak isteyen kişilerin başvurabileceği kaynaklar çok sınırlıdır. Çalışmamızda önerilen ve yasanın da çıkmasıyla son şeklini alan Türk mortgage sisteminde konut kredileri; bankalar, katılım bankaları, tüketici finans şirketleri ve finansal kiralama şirketleri tarafından açılabilmektedir. Bu çerçevede çalışmanın özellikle son bölümünde de görüleceği gibi, Türkiye.de çok uzun yıllardır, yüksek enflasyon ve dolayısıyla yüksek faiz oranları ile mücadele edildiği için, konut sektörü ve bir finansman tekniği olan mortgage-ipotekli konut finansmanı hep ihmal edilmiştir. Enflasyon problemini çözmüş olan, sadece gelişmiş değil, Türkiye.den daha düşük kişi başına milli gelir düzeyine sahip bazı ülkelerde dahi mortgage-ipotekli konut finansmanı sisteminin işlediği görülmektedir. Türkiye için çok büyük yenilik olan ikinci el ipotek piyasasının zamanla gelişmesi ile birlikte, değişik tiplerdeki ipoteğe dayalı menkul kıymetleştirme türlerinin uygulanmasına olanak sağlayacak ve ülkemiz ekonomisinin çok daha iyi yerlere gelmesine imkan tanıyacaktır.

The common goal and the major focus of housing finance systems is providing funds for households to buy their own houses. In order to fulfill the funding requirement of low/ middle income groups, housing finance system offers basically two alternatives. For the countries which does not have a developed housing finance system, people usually borrow funds from their relatives within the context of traditional social support mechanism of family relations which is called direct finance . However in line with the economic development, when there is an effective housing finanace system exists, even modest income groups borrow funds from financial institutions utilizing the mortgage loan facilities. In general terms, the mortgage market has two faces, the primary and the secondary markets. The primary market covers housing mortgage loans. On the other side of the mechanism, these loans are securitized and issued in financial markets with different form of securities in secondary markets. The common name of these instruments is mortgage backed securities - MBS . A mortgage backed security is a financial instrument issued in capital markets for investors, derived from either backed by the cash flow of the housing loan repayments (which is called pay-through) or backed by directly selling the mortgage pools to the MBS issuers (which is called pass-through) . The major difference of mortgage system from the direct housing loan mechanism is it s ability of self-funding suffeciency. The banking industry and the other financial institutions who are authorized to allocate housing loans with the repayment guarantee of mortgages, build mortgage pools considering the major uniform characteristics of these loans (i.e. termination of the loans, specific housing projects). With the help of the cash flow from loan and interest repayments, the passthrough or pay-through mortgage backed securities are issued in capital markets by authorized financial institutions. The issue income from MBS is the major source of the new mortgage loans, therefore the system has self-growing facility. Regarding the low marginal propensity to save multiple of the household economy, the Turkish financial system offers limited alternatives and funding facilities for housing finance. The banking industry which is the major power behind our financial system, can only utilize YTL and FX deposits and syndication facilities from foreign banks in order to fund housing loans. Therefore, a great deal of termination and currency mismatch risk appears in the balance sheet of the banking system as a consequence of these operations. The infant Turkish Mortgage System which has been in effect since a couple of months offers a new horizon for both supply and demand sides of the housing finance. According to the new mortgage legislation, apart from the banks which still will be the major engine of the housing finance, financial leasing and consumer finance companies can also utilize mortgage facility loans. As indicated in the last part of our study, despite the fact that the falling inflation and interest rates from unbearable to the modest levels in recent years, these indicators are still too high for the healty operation of our mortgage finance system. As a consequence of these high levels of inflation and interest rates, housing finance in general and mortgage finance was neglected over the past decades. Even the developing countries which have lower per capita GNP than Turkey, could operate their mortgage finance system with both primary and secondary markets due to their lower levels of inflation rates. Turkey is now facing with the problem of building the secondary mortgage markets in order to make a self-sufficient housing finance system. Our prospective secondary mortgage market will introduce new investment vehicle alternatives for the investors who are still continue to play with company stocks and fixed income state bonds. This mission will be a new era for the development of the Turkish economy and financial markets. In our study we tried to envisage the basic operation of our prospective mortgage finance system. Within this context, we tried to discover the interrelations among the financial institutions and their products which will be intoduced in the primary and secondary mortgage markets. We also tried to build a simple model for the operation of pass-through and pay-through mortgage bonds related to Housing Finance Funds (KFF) and Mortgage Finance Institutions (IFK).
Keywords: Bankalar ve Bankacılık_Mortgage; Gayrimenkul_Türkiye; Konut Politikası_Türkiye